The “LEADER Approach” - New Development Opportunity for Rural Areas in Slovenia - Cunder, Tomaž; Bedrač, Matej (Journal for Geography, 2010)
Integrated rural development programmes, which are prepared with the active involvement of local citizens, have a long tradition in Slovenia. In the period 1991-2006, Slovenia introduced “Programmes of Integrated Rural Development and Village Renewal” and “Development Programmes for Rural Areas”, which were quite similar to the LEADER initiative in the European Union. From the 2007-2013 programming period, the LEADER approach has been mainstreamed within the overall EU rural development policy. This means that LEADER is included in national and regional rural development programmes supported by the EU, alongside a range of other rural development axes. The main emphasis of the current paper is given to the implementation of the LEADER approach and establishment of local action groups in the 2007-2013 programming period. The paper consists of three parts. The first part presents the general characteristics of the LEADER approach and the measures which are carried out in the 2007-2013 Rural Development Programme. In the second part, an analysis of 33 Local Action Groups is described. The main focus is given to spatial-demographic characteristics, the partnership structure, and the organisation of the decision making body. The paper concludes with an analysis of 33 Local Development Strategies. We analysed the extent to which the strategic goals and priority tasks of Local Development Strategies follow the economic, social and spatial-environmental component of sustainable development.
Keywords: rural development; agricultural policy; LEADER approach; local action groups, structure of partnership; local development strategies